2D Conductive Metal–Organic Frameworks: An Emerging Platform for Electrochemical Energy Storage. Issue 11 (20th August 2020) - Liu, Jingjuan; Song, Xiaoyu; Zhang, Ting; Liu, Shiyong; Wen, Herui; Chen, Long
Abstract: Two‐dimensional conductive metal–organic frameworks (2D c‐MOFs) as an emerging class of multifunctional materials have attracted extensive attention due to their predictable and diverse structures, intrinsic permanent porosity, high charge mobility, and excellent electrical conductivity. Such unique characteristics render them as a promising new platform for electrical related devices. This Minireview highlights the recent key progress of 2D c‐MOFs with emphasis on the design strategies, unique electrical properties, and potential applications in electrochemical energy storage. The thorough elucidation of structure–function correlations may offer a guidance for the development of 2D c‐MOFs based next‐generation energy storage devices. Abstract : Thanks to their predesigned structure, intrinsic porosity and decent conductivity, 2D c ‐MOFs have attracted considerable attention especially in electrochemical energy storage. In this Minireview, the progress of 2D c ‐MOFs is surveyed with a focus on the structural design principles, electrical properties and potential applications in supercapacitors and batteries.